Birth during the Pandemic: Makassar City Government Policy towards the Surging Birth Rate During the COVID-19 Pandemic - Syam, Febrianto; Rukmana, Novayanti Sopia; Fajar, Desi Reski (Pinisi Journal of Social Science, 2025)
The COVID-19 pandemic has had a major impact on various aspects of people's lives, including population dynamics. In Makassar City, there has been a significant increase in the birth rate during the pandemic which has posed challenges for the city government. This research aims to analyze how the Makassar City government's policies respond to the increasing birth rate and its impact on society. This research uses a descriptive qualitative approach with policy analysis based on literature and secondary data. The research results show that the policies implemented during the pandemic have not been fully responsive to community conditions, especially in terms of access to contraceptive services and family planning education. Improvement efforts are needed in planning and implementing population policies during times of crisis so that community welfare is maintained.